2019
DOI: 10.3139/146.111777
|View full text |Cite
|
Sign up to set email alerts
|

Effects of graphene nanoplatelets on the tribological, mechanical, and thermal properties of Mg-3Al alloy nanocomposites

Abstract: The present research investigated the tribological and the thermal properties of Mg-3Al-xGNP alloy nanocomposites, fabricated through a powder metallurgy route with microwave assisted sintering followed by hot extrusion. Graphene nanoplatelets (GNPs) were incorporated as reinforcements in different amounts (0.1 wt.%, 0.3 wt.%, and 0.5 wt.%) into pure Mg and Mg-3Al alloy. The values of coefficient of friction and wear rate of pure Mg, Mg-3Al alloy, and Mg-3Al/xGNPs (x = 0.1 wt.%, 0.3 wt.%, and 0.5 wt.%) nanocom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Worn surface analysis reveals abrasion and adhesion as dominant wear mechanisms which transit to thermal softening at highest sliding speed. Graphene nano platelets (width 5 μm and thickness 2–10 nm) of varying amount (0.1, 0.3 and 0.5 wt.%) were incorporated in pure Mg and Mg–3Al using powder metallurgy by Kumar et al 35 Pin-on-disc type tribometer was employed to investigate tribological characteristics of those nanocomposites considering different parameters. Nanocomposite reinforced with 0.3 wt.% GNP was found to yield best tribological and mechanical properties.…”
Section: Dry Sliding Wear Behaviourmentioning
confidence: 99%
“…Worn surface analysis reveals abrasion and adhesion as dominant wear mechanisms which transit to thermal softening at highest sliding speed. Graphene nano platelets (width 5 μm and thickness 2–10 nm) of varying amount (0.1, 0.3 and 0.5 wt.%) were incorporated in pure Mg and Mg–3Al using powder metallurgy by Kumar et al 35 Pin-on-disc type tribometer was employed to investigate tribological characteristics of those nanocomposites considering different parameters. Nanocomposite reinforced with 0.3 wt.% GNP was found to yield best tribological and mechanical properties.…”
Section: Dry Sliding Wear Behaviourmentioning
confidence: 99%
“…Superfluous tool wear may cause excessive heat generation in the machining part during machining process. Pravir et al [ 41 ] demonstrated a comprehensive study on the mechanical, thermal and wear behavior of Mg-nanocomposites. Furthermore, the traditional machining technique causes serious tool wear during the processing of MMNCs and results in higher surface roughness, which restricts the application of these composites.…”
Section: Introductionmentioning
confidence: 99%
“…Graphene nanoplatelets (GNPs) is derivative of graphite and consists of multiple layers of graphene. It retains many appealing properties of single layer graphene and exhibits superior mechanical, thermal, electrical, and tribological properties [29,30]. GNPs has the potential to significantly improve the performance of different metals (Mg, Al, Cu, Fe, Ni), alloys, and intermetallic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Khurram Munir et al [37] fabricated Mg-GNP MMCs with different graphene contents (0.1, 0.2, and 0.3 wt.%) and obtained positive results in terms of compression, corrosion, and biocompatibility. Kumar et al [30] fabricated Mg-3Al/xGNP (x = 0.1, 0.3, and 0.5 wt.%) alloy-nanocomposites with improved mechanical and tribological properties. The incorporation of GNP improved coefficient of thermal expansion (CTE) (owing significant CTE difference between Mg and GNP) and ignition characteristics of the nanocomposites.…”
Section: Introductionmentioning
confidence: 99%